ATHEROSCLEROSIS RISK FACTORS IN WOMEN DURING MENOPAUSE - Petrovska, Sunchica; Dejanova, Beti; Manchevska, Sanja; Pluncevic Gligorova, Jasmina (Journal of Morphological Sciences; Vol 1 No 1 (2018): JMS, 2018)
The loss of female sex hormones after menopause contributes to the striking increase in the incidence of cardiovascular morbidity and mortality. The present study was designed to evaluate some of the artherosclerotic risk factors: LDL-C, HDL-C and factor VII of coagulation, in women during menopause.                                                                    The study comprised a number of 77 women divided into three groups. The control group included 25 healthy women in their reproductive period. The perimenopausal group consisted of 27 women, with FSH level under 25mU/ml, and with anamnestic data of irregularity of menstrual cycle. The postmenopausal group encompassed 25 women regarding lack of cycle for more than 12 months. Hormone level was determined with RIA method. Lipid level was determined with standard colorimetric-spectrophotometric method  and the concentration of f. VII was determined by method of plasma deficiency. Statistical analysis has shown that there was a significant increase of LDL-C and factor VII in both perimenopausal and postmenopausal examines in comparison with the control group (p<0,001). This study favours the view that decrease in estradiol level and associated increase in LDL-CH and factor VII seen in perimenopausal and postmenopausal women may be responsible for the increased risk of atherosclerotic thromboemembolic complications in women during the most vulnerable period of their life.